Governmental interference in Intellectual Property rights for Covid-19 vaccines and historical conditions for medical product exportation within the context of the US and the EU - Teļnova, Patrīcija (Riga Graduate School of Law, 2022)
The paper analyses Patent law in the US, comparing the systems between the US and the EU. With academic article analysis, the paper presents the issue of the Covid-19 vaccine supply shortage in low-income countries, as well as underlines the diplomatic alliances of the EU and US, the reasons why such alliances are made and how they sustain each other. Thesis research how the US can manage a patent waiver in times of pandemic to supply low-income countries the coronavirus vaccines, which is supplemented with an analysis of the TRIPS agreement as well the United States patent law. The study's objective is to find out how a patent waiver can be imposed under certain circumstances and why it has not been implemented mentioning the main obstacles and presenting an alternative - compulsorily licensing. The second objective of the research is to find out how a patent waiver could be granted in Europe with the AstraZeneca vaccine, and what countries would benefit the most from such a waiver of the coronavirus vaccine.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law::Intellectual property law; Patent law; Covid-19 vaccine; The United States; The European Union